2017
DOI: 10.3389/fmicb.2017.01586
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Oenococcus oeni SD-2a Response to Acid Shock by RNA-Seq

Abstract: Oenococcus oeni can be applied to conduct malolactic fermentation (MLF), but also is the main species growing naturally in wine. Due to the high stress tolerance, it is an interesting model for investigating acid response mechanisms. In this study, the changes in the transcriptome of O.oeni SD-2a during the adaptation period have been studied. RNA-seq was introduced for the transcriptomic analysis of O. oeni samples treated with pH 4.8 and pH 3.0 at 0 and 1 h, respectively. Gene ontology (GO) and Kyoto encyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…In 16% ethanol, the top-ranked gene was proC , which was not evaluated in the previous studies of O. oeni , whereas gyrB and dnaG were ranked second and third respectively. In our study, dpoIII, dnaG, gyrB , and gyrA showed better expression stability, while in some studies, they were used together as reference genes for RT-qPCR normalization in O. oeni , but not evaluated particularly (Costantini et al, 2011 ; Margalef-Català et al, 2016 ; Liu et al, 2017 ). Moreover, the traditional reference genes in O. oeni , such as ddlA and ldhD varied greatly in our experimental conditions.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In 16% ethanol, the top-ranked gene was proC , which was not evaluated in the previous studies of O. oeni , whereas gyrB and dnaG were ranked second and third respectively. In our study, dpoIII, dnaG, gyrB , and gyrA showed better expression stability, while in some studies, they were used together as reference genes for RT-qPCR normalization in O. oeni , but not evaluated particularly (Costantini et al, 2011 ; Margalef-Català et al, 2016 ; Liu et al, 2017 ). Moreover, the traditional reference genes in O. oeni , such as ddlA and ldhD varied greatly in our experimental conditions.…”
Section: Discussionmentioning
confidence: 78%
“…The O. oeni SD-2a was cultured at 28°C and pH 4.8 in three flasks with 100 mL FMATB broth, which contains glucose 5 g/L, D, L-malate 5 g/L, yeast extract 5 g/L, peptone 10 g/L, MgSO4 •7H 2 O 0.2 g/L, MnSO4 •4H 2 O 0.05 g/L, Cysteine/HCl 0.5 g/L, and tomato juice 250 mL (Li et al, 2009 ; Liu et al, 2017 ). The growth of cultures was monitored by measuring OD value using a spectrophotometer (Cary 60 UV-Vis, Agilent Technologies, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a similar approach can be employed to tackle the metabolic response to acidic conditions in this bacterium, which, together with alcohol and SO 2 stresses, are the most relevant conditions that affect the growth of O. oeni. For instance, Liu et al (2017) recently showed, using RNA-seq, that in O. oeni SD-2a strain grown at pH of 4.8 and pH 3.0, several genes related with the metabolism of amino acids, carbohydrates, membrane transport and energy metabolism were differentially expressed. Therefore, the resulting quantitative transcriptomics can be incorporated into the iSM454 metabolic model as restrictions and, together with experimental data, could allow to simulate the redistribution of metabolic fluxes resulting from this environmental perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…Proline iminopeptidase (pip), associated with arginine and proline metabolism, was highly downregulated in LR in all stages. As proline (and pip) concentrations tend to increase under stress in a broad range of living organisms 40,54,55 , we would expect the pip gene to be upregulated. It should be noted that we did observe a high accumulation of L-proline in the ripe LR fruit.…”
Section: Discussionmentioning
confidence: 99%